Modern problems of environment in operation and repair aviation technology - Драч, О.Ю.; Франчук, Г.М. (Proceedings of National Aviation University (archive), 2006)
It was learnt the negative effect of oil pollution on soil microorganisms in the zone of the airport activity. Factor-analysis of soil fermentative activity in the environment of heavy metals and oil products was done. There is ecologo-economical valuation of the soil affected by lasting aircraft activities and airport services. Mathematical model envisages the soil alive phase stability on the territories close to the airport.